Empowering Productive-Age Women Groups in Nagari Batu Bulek through Marketing of Traditional Food Integrated with Online Tour Packages - Hidayati Hidayati; Fauziah Ulmi; Emiliannur Emiliannur; Hayyu Yumna; Hufri Hufri (Pelita Eksakta, 2026)
The objective of this community service activity is to equip productive-age women with the necessary skills to package food, obtain PIRT (household food industry) licenses, develop product branding, and market traditional food by utilizing social media, websites, and e-commerce platforms integrated with online tour packages. This initiative indirectly contributes to improving the economic welfare of women in Batu Bulek and preserving the region’s traditional food. The skill development program for productive-age women groups in Nagari Batu Bulek in marketing traditional food integrated with online tourism packages was carried out through several stages, namely the preliminary stage, preparation, and implementation. The results showed an increase in participants’ understanding with an N-gain score of 0.36, which falls into the medium category. This activity also received positive responses from the participants, as indicated by the satisfaction survey with an average score of 93.7. Through this training program, productive-age women in Nagari Batu Bulek gained knowledge and skills in food packaging and product branding.